Предмет: Математика,
автор: ievavanaga21
(b-1) (b +1)-(a+1)(a-1)
Ответы
Автор ответа:
0
Ответ:
или
Автор ответа:
0
Відповідь:
b²-a²
Покрокове пояснення:
(b-1) (b +1)-(a+1)(a-1)=b*b+b*1-1*b-1*1-(a*a+a*(-1)+1*a+1*(-1))=b²+b-b-1-(a²-a+a-1)=
b²-1-(a²-1)=b²-1-a²-(-1)=b²-1-a²+1=b²-a²=(b-a)(b+a)
Похожие вопросы
Предмет: Русский язык,
автор: dyavid1999
Предмет: Английский язык,
автор: k1sska71
Предмет: Українська мова,
автор: vitali12
Предмет: Математика,
автор: sobakygmailcom
Предмет: Математика,
автор: mmaksimm102